Kriminalisasi di Luar KUHP dan Implikasinya terhadap Hukum Acara Pidana - Rizanizarli Rizanirarli (Kanun Jurnal Ilmu Hukum, 2014)
The Renewal and the development of the national legal system, including the criminal law and criminal procedure law, is one of the major issues on the political agenda in Indonesian law and should be done immediately. The concept of the New Criminal Code has been exposed, but until now it has not been completed with a variety of problems because there is no agreement in several aspects.  The Criminal Procedure Code is a masterpiece of Indonesia creation, it also needs to be harmonized with the development given the growing globalization of crime. For peace and law certainty of law in preventing crime and to avoid a legal vacuum will be needed in the criminalization of certain criminal acts. Outside Criminal Code Criminalization and Its Implications of Criminal  Procedure Code